COMPARISON STUDY OF ARDUINO TECHNOLOGY BETWEEN UNO AND WEMOS D1 FOR SMART HOME SYSTEMS BASED ON IOT - Adam Antis, Tony (Universiti Malaysia Sarawak (UNIMAS), 2020)
One of the Arduino technology which is the Arduino Uno are the most favorite used by Arduino user as its microcontroller to control the features of smart home. In recent years, a newer Arduino technology, Arduino WEMOS D1 has been invented where its hardwares resemble the Arduino UNO in terms of its board. It is assumable that newest technology is better compare to its predecessor. However, many Arduino users still chose Arduino UNO as the favorite Arduino technology for their projects. This leads to the objective of this study is conduct which is to compare the capabilities between Arduino UNO and Arduino WEMOS D1 in terms of its memory, speed of processor and power usage so that Arduino users know which Arduino technology is better to their project and this study will show which technology is cost effective because the outcome of this study will show which Arduino has less power usage but with greater memory and speed of processor. This is beneficial to Arduino user out there that need a great Arduino technology but with less power usage that will help in reducing the electricity bill. Overall, this report introduces the background of the study, methodology used and designs of the system. Once a fully functional smart home system with Arduino UNO and WEMOS D1 have been developed, then the comparison between the Arduinos can be done.